THE SERVANT LEADERSHIP OF SCHOOL ADMINISTRATORS AFFECTING TEAMWORK OF TEACHERS IN PRIVATE SCHOOL MUANG NAKHON RATCHASIMA DISTRICT - Pinichpong , Yordkwan; Pechrpuang, Sopon (Journal of MCU Nakhondhat, 2023)
The purposes of this research article were to study 1) the level of the Servant leadership of School administrators in private school Muang Nakhon Ratchasima District 2) the level of the teamwork of Teachers in Private School Muang Nakhon Ratchasima District and 3) the servant leadership of school administrators affecting teamwork of teachers in private school Muang Nakhon Ratchasima District. It is quantitative research of the population including 1,060 teachers from 43 schools. The sample were 285 teachers in private school. Selected from Systematic random sampling, a tool for this research was the reliability questionnaire 0.89 analysis with basic statistics, average and standard deviation, and test statistic, multiple regression analysis. The finding were: 1) The servant leadership of private school administrators Mueang Nakhon Ratchasima District consists of Overall, it was at a high level. And when considering each aspect, it was found that all aspects were at a high level as well, the highest average is Commitment to the growth of people, the lowest average is Listening. 2) Teacher teamwork in a private school Mueang Nakhon Ratchasima District Overall, it was at a high level. And when considering each aspect, it was found that all aspects were at a high level as well, the highest average is Coordination, the lowest average is Communication. 3) The Servant Leadership of School Administrators Affecting Teamwork of Teachers in Private School Muang Nakhon Ratchasima District. found that the variables that could predict the service-oriented leadership of administrators affecting the teamwork of teachers in private schools. Mueang Nakhon Ratchasima District, there are 7 variables, namely Commitment to the growth of people, Healing, Awareness, Empathy, Persuasion, Building Community and Listening statistically significant at the .05 level and There were able to jointly predict the teamwork of teachers in private schools, 88.70 percent. Therefore, administrators and teachers should have good human relations. Build strength to improve the quality of life